CLIL Teacher training at the UPCT: present and future within the EHEA - Camino Rea Rizzo; Natalia Carbajosa Palmero (Universitat Politècnica de València, 2014)
Throughout the last decades of the twentieth century and the beginning of the twenty-first, the teaching of English for specific and/or professional and academic purposes has probably constituted one of the most innovative areas in the Spanish University. With the advent of the Bologna reform, the theory and praxis of this dynamic field of knowledge has enhanced its range of activity, so as to include not only students, but also lecturers, whithin its concerns. The result can be measured by the innumerable variety of CLIL (Content Language Integrated Learning) teacher training experiences carried out along the Spanish Tertiary Education geography. This paper has two main purposes: on one hand, to give the account of the CLIL teacher training at the UPCT (included in the larger frame of teaching innovation programs), under its corresponding theoretical approach and bearing in mind the particular circumstances of the institution. On the other hand, to pose questions about the future perspectives of similar experiences in a teaching context that is becoming more and more complex and `hybrid´ from its very foundations. The partial conclusions of this study depict a global teaching/professional scenario that is both challenging and appealing, which must be seriously dealt with from the Universities and our common European administrative framework alike. RESUMEN Formación CLIL del profesorado en la UPCT: presente y futuro dentro del EEES. The objective of this article is to describe an experimental study about a collaborative learning experience carried out on the Degrees in Pedagogy and Primary School Education at the University of Barcelona (UB). Specifically, we analyze the implementation of “Collaborative Seminars” in two core subjects. The aims of this project were to boost team working skills amongst students at the same time as encouraging acquisition of core contents in both subjects. Firstly, we discuss the theoretical models which motivated the project and underlaid many of the decisions taken by the training team. Secondly, we offer detailed information on the specific features adopted by the seminars and on how the project developed over one semester. Finally, we describe how data was collected and present the results. To assess the experience we used a variety of information-gathering strategies such as questionnaires, discussion groups and participant observation. Results show, amongst other things, that collaborative seminars contribute to the learning of significant course contents, to the acquisition of various communication skills, to the development of the learning to learn competence, and to the encouragement of personal and interpersonal team working abilities. Lastly, our study reveals the problems and hindrances we came across when implementing the group seminars, and suggests some ideas in order to make future improvements.